POLICY AND STRATEGY FOR E-GOVERNMENT DEVELOPMENT IN JEMBER DISTRICT (IMPLEMENTATION OF INPRES NO. 3 / 2003) - Iffan Gallant El Muhammady; Ahmad Suryono; Haressa Lintang Rizkika; Robit Syaifan Nawas (POLITICO, 2022)
The purpose of this research is to describe and analyze and identify aspects that hinder the implementation of the Presidential Instruction no. 3 of 2003 in Jember Regency. This research uses a qualitative research type with purposive technique. The theory refers to the Implementation of Donald Van Meter and Van Horn and Daniel A. Mazmanian Paul A. Sabatier. The results of this study indicate that the implementation of Presidential Instruction No. 3 of 2003 is still running relatively well. The limited understanding of the implementor, financial resources and human resources as well as the inequality of the socio-political, economic and technological conditions are factors that are less than optimal in the results achieved by the Jember Regency Government. The recommendations for this implementation are increasing the understanding of implementors by conducting socialization, increasing the quality and quantity of human resources with trainings in the field of information technology, providing adequate infrastructure, the need for a clear legal umbrella (PERDA), and the need to simplify the applications developed. Regional Government of Jember Regency.